Quality Assurance in Open and Distance Learning: Strategies and Approaches from the Perspective of Open University Malaysia - Anuwar Ali (2014)
Over the last several decades, higher education in many countries has been significantly transformed; with various new institutions established and many novel academic programmes now on offer. This is a common worldwide development; reflecting the universal focus on higher education as a national investment for economic progress and building human capital. This rapid growth and expansion are accompanied by an equal concern for quality, particularly in an environment where private higher education entities, including open universities and open and distance learning (ODL) institutions, are becoming prominent providers of learning opportunities for the masses. In this regard, ensuring quality is critical, as ODL has become synonymous with educating working adults – individuals who, as members of a nation’s labour force, are instrumental to national development. Additionally, the increasing influence of information and communication technology (ICT) on educational practices has also called for more rigorous and stringent quality assurance (QA) systems and procedures. QA is important as a means to establish standards and accountability; ensure learner satisfaction; and enhance institutional image and prestige. As Malaysia’s premier open university, Open University Malaysia’s (OUM) understanding of QA stems from a holistic institutional approach that emphasises learner-centredness. This keynote address will discuss the strategies and approaches that OUM has adopted to create a QA system that complies with existing national guidelines, while exploring the development of a quality concept that is suited to the unique nature of ODL. This paper will also discuss how benchmarking and adopting best practices can contribute to a more well-rounded approach that can benefit open universities and other higher education institutions across the region. (Abstract by author)